Leonel Alvarado Fundraiser with Governor Jerry Brown at Fresno Fairgrounds Building - Watkins, Howard::::::::: (1982)
Governor Jerry Brown with Christine Watkins, Adam Watkins, and Alicia Cordova Leonel Alvarado and Victor Salazar in background